Post-Mortem Analysis of the 2016 Election Based on the Political Marketing Strategies Used by Local Political Parties in Dumaguete City - Catapusan , Eduard (Journal of Interdisciplinary Perspectives, 2024)
This research study is a post-mortem analysis of the 2016 local elections in Dumaguete City, focusing on the political marketing strategies used by the Liberal Party (LP) and Nationalist People’s Coalition (NPC) candidates. The objective was to analyze the political marketing strategies the political parties and candidates employed in the 2016 elections. It also aimed to address the research gap by systematically examining and analyzing the political marketing practices within the local context. The researcher employed a combination of descriptive-quantitative and qualitative designs. The quantitative design was facilitated by measuring the level of effectiveness of the political marketing strategies used by the party and the candidates to win votes, which was measured on a scale of 5.00, where 1.00 is not effective, and 5.00 is the most effective. The qualitative design was facilitated by the archival of documents and structured interviews. The study's respondents were the mayor, vice mayor, and ten city councilors, totaling 12 (n=12). However, only 9 (n=9) participated in answering the survey questionnaire and guide interview. Using Menon’s framework, the study found that LP dominated the election, employing strategies like clear platforms, candidate image building, party disclosure, information drives, material rewards, smart slogans, and social media use. They also managed attitudinal and behavioral barriers effectively. LP’s dominant strategies included media campaigns, house-to-house campaigns, public forums, small group meetings, and leaflet distribution. NPC, on the other hand, focused on good governance, transparency, and monetary indulgence. Both parties utilized product function, distribution function, cost function, machine politics and rewards, news management function, and communication function. The top three effective strategies were the news management function (4.61), product function (4.59), and communication function (4.58). The study concluded that LP was more thorough and organized in its marketing strategy application, giving them critical advantages in the election.